Inhibition of human glioma cell proliferation by altered Bax/Bcl-2-p53 expression and apoptosis induction by Rhaponticum carthamoides extracts from transformed and normal roots. (2nd October 2016) - Skała, Ewa; Sitarek, Przemysław; Toma, Monika; Szemraj, Janusz; Radek, Maciej; Nieborowska-Skorska, Malgorzata; Skorski, Tomasz; Wysokińska, Halina; Śliwiński, Tomasz
Abstract: Objective: The objective of this study was to determine the cytotoxic effect and apoptotic activity of Rhaponticum carthamoides transformed root (TR) and root of soil-grown plant (NR) extracts in a human glioma primary cells. The effect of these root extracts on cell cycle arrest, mitochondrial membrane potential (ΔΨm) and expression levels of apoptosis-related genes (Bcl-2, Bax and p53) were also examined. Methods: Cytotoxic activity of root extracts was evaluated by MTT assay. Apoptosis and cell cycle were determined by flow cytometry. Expression levels of apoptosis-related gene were analysed by RT-PCR and Western blotting. ΔΨm was examined by the use of JC-1 reagent. Key findings: Rhaponticum carthamoides root extracts inhibit cell growth and induce apoptosis in a dose-dependent manner in human glioma cells. The root extracts were found to up-regulate the pro-apoptotic Bax protein and down-regulate the anti-apoptotic Bcl-2 protein, consequently increasing the ratios of Bax/Bcl-2 protein levels. Moreover, an increase of the p53 protein level and reduction of ΔΨm in glioma cells were observed after treatment with NR and TR extracts. Conclusion: The results of this study may offer a new insight into the potential anticancer activity of R. carthamoides root extracts.